1992
DOI: 10.1128/aac.36.1.153
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus type 1 pol gene mutations which cause decreased susceptibility to 2',3'-dideoxycytidine

Abstract: To investigate whether human immunodeficiency virus type 1 pol gene mutations are selected during prolonged 2',3'-dideoxycytidine (ddC) therapy, we used the polymerase chain reaction to amplify a portion of the reverse transcriptase segment of the pol gene from the peripheral blood mononuclear cell DNA of a patient with AIDS before and after an 80-week course of ddC therapy. The consensus sequence from the second sample contained a unique double mutation (ACT to GAT) in the codon for reverse transcriptase amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
0
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(110 citation statements)
references
References 25 publications
5
104
0
1
Order By: Relevance
“…The T69D was detected in 1 child. It causes resistance to ddC (Fitzgibbon et al 1992) and contributes to the NRTIs resistance when occurring together with NEMs (Winters et al 2001). The L74V, reported in 2 children, occurs commonly during ddI and ABC monotherapy (Miller et al 2000) and confers 2 to 5-fold resistance to ddI and ddC (Winters et al 1997) and 2 to 3-fold resistance to ABC (Tisdale et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The T69D was detected in 1 child. It causes resistance to ddC (Fitzgibbon et al 1992) and contributes to the NRTIs resistance when occurring together with NEMs (Winters et al 2001). The L74V, reported in 2 children, occurs commonly during ddI and ABC monotherapy (Miller et al 2000) and confers 2 to 5-fold resistance to ddI and ddC (Winters et al 1997) and 2 to 3-fold resistance to ABC (Tisdale et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…AZT-resistant mutations occur in a pocket that is connected to the triphosphate binding region of the active site (Fig. 1, region I) (33,34,43). Reports have shown that AZTresistant mutations, in the absence of causing large changes in incorporation (25,35), may cause an increase in the rate of pyrophosphorolysis (36) and ATP-mediated removal (34,37).…”
Section: Compounds Currently Approved By the Food And Drug Administramentioning
confidence: 99%
“…Human immunodeficiency virus (HIV) isolates resistant to many compounds targeted to the virus-encoded enzyme reverse transcriptase (RT) have been identified during drug therapy or by selection in vitro (Fitzgibbon et al, 1992;Larder, 1992;Nunberg et al, 199 l ;Richman et al, 1991a;St Clair et al, 1991). Variants of HIV highly resistant to zidovudine (AZT, Retrovir) have been isolated from AIDS patients receiving prolonged treatment (Boucher et al, 1990;Land et al, 1990;Richman et al, 1990;Rooke et al, 1989).…”
Section: Introductionmentioning
confidence: 99%